Periodic Disease In Children. Clinical Case (Texas Journal of Multidisciplinary Studies, 2024)
Patients with periodic disease (PD) are quite common in certain ethnic groups. However, the relevance of the topic is also due to the early onset of the pathology and, in most cases, a serious prognosis for the patient's life, provided the disease is detected and treated late. Often, diagnostic errors can lead to unjustified surgical interventions